Gender-specific outcomes of bladder cancer patients: A stage-specific analysis in a contemporary, homogenous radical cystectomy cohort. Issue 3 (March 2015) - Soave, A.; Dahlem, R.; Hansen, J.; Weisbach, L.; Minner, S.; Engel, O.; Kluth, L.A.; Chun, F.K.; Shariat, S.F.; Fisch, M.; Rink, M.
Abstract Introduction Controversial findings regarding gender-specific oncological outcomes of urothelial carcinoma of the bladder (UCB) have recently been reported. The aim of this study was to analyze gender-specific outcomes using a stage-adjusted approach in a homogenous, contemporary radical cystectomy (RC) cohort. Material and methods We prospectively collected data of 517 UCB patients treated with RC and pelvic lymphadenectomy without neoadjuvant chemotherapy at our institution between 1996 and 2010. Stage-adjusted uni- and multivariable Cox regression models analyzed the association of gender with disease recurrence, cancer-specific mortality and overall survival. Results In total, 398 (77%) patients were male and 119 (23%) were female. Compared to men, women were more likely to have advanced tumor stages (p = 0.017), nodal metastasis (p = 0.047) and received more frequently adjuvant chemotherapy (p = 0.009). At a median follow-up of 44 months, there was no statistical difference in disease recurrence, cancer-specific mortality and overall survival between both genders when analyzed as a group. In stage-adjusted analyses, only women with non-invasive UCB were more likely to die of UCB compared to the male counterparts (p = 0.013). In gender-specific multivariable analyses that adjusted for standard clinico-pathologic features, pathologic tumor stage was an independent predictor for disease recurrence (p-values ≤0.047) and cancer-specific mortality (p-values ≤0.049), respectively. Conclusion Women present with more aggressive tumor biologic features at RC, however this did not translate into inferior outcomes compared to men in stage-specific analyses in our cohort. Tumor stage is the most important factor influencing the course of disease in both genders. Validation of our findings is warranted in a larger cohort.